Charge Transfer across the Interface between LiNi0.5Mn1.5O4 High-Voltage Cathode Films and Solid Electrolyte Films. Issue 4 (1st January 2015) - Gellert, Michael; Gries, Katharina I.; Zakel, Julia; Kranz, Sebastian; Bradler, Stephan; Hornberger, Elisabeth; Müller, Sandra; Yada, Chihiro; Rosciano, Fabio; Volz, Kerstin; Roling, Bernhard
Abstract : We have carried out a basic study on the charge transfer across the interface between LiNi0.5 Mn1.5 O4 (LNMO) thin-film cathodes and different solid electrolyte coatings, namely LiNbO3, ZrO2 and Li4 Ti5 O12 . In contact to LNMO, the spinel material Li4 Ti5 O12 should act as a solid electrolyte, since it exhibits a very low electronic conductivity in the fully oxidized state. The thin films were prepared by means of sol-gel chemistry and spin-coating. The electrochemical and interfacial properties were studied by combining electrochemical impedance spectroscopy (EIS), time-of-flight secondary-ion mass spectrometry (ToF-SIMS) and cross-sectional SEM imaging. The results show that the LNMO / LiNbO3 interface combines a low charge transfer resistance with a high stability.